2017
DOI: 10.1111/jbi.13085
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity within populations of an arctic–alpine species declines with decreasing latitude across the Northern Hemisphere

Abstract: Aim We identified and evaluated general latitudinal trends in genetic diversity within populations of a widespread arctic–alpine plant, Dryas octopetala, to examine the applicability to this species of the dominant hypothesis that intraspecific genetic diversity is highest in the tropics and declines towards the poles. Location The circumpolar Arctic and northern temperate alpine ranges, with a focus on high altitude mountains at the species lowest latitudinal margin in the Japanese archipelago. Methods Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 66 publications
3
19
1
Order By: Relevance
“…Moreover, the contrary is observed here, with a latitudinal cline of genetic variation in northern areas and lower values in southern areas. This pattern, which has been reported in some cold-adapted species (Hirao et al, 2017), as well as in other salmonids (Ninua et al, 2018) and other anadromous species (Hasselman et al, 2013), has also been expected in S. salar (Valiente et al, 2005), but it had been found only for major histocompatibility complex class II genes (Dionne et al, 2007); to our knowledge, our study is the first report of the pattern for microsatellite markers in this species. Thus, anadromous species appear to exhibit the opposite of the pattern that usually occurs in vertebrates (Adams & Hadly, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the contrary is observed here, with a latitudinal cline of genetic variation in northern areas and lower values in southern areas. This pattern, which has been reported in some cold-adapted species (Hirao et al, 2017), as well as in other salmonids (Ninua et al, 2018) and other anadromous species (Hasselman et al, 2013), has also been expected in S. salar (Valiente et al, 2005), but it had been found only for major histocompatibility complex class II genes (Dionne et al, 2007); to our knowledge, our study is the first report of the pattern for microsatellite markers in this species. Thus, anadromous species appear to exhibit the opposite of the pattern that usually occurs in vertebrates (Adams & Hadly, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…This pattern, which has been reported in some cold‐adapted species (Hirao et al . , ), as well as in other salmonids (Ninua et al ., ) and other anadromous species (Hasselman et al ., ), has also been expected in S. salar (Valiente et al . , ), but it had been found only for major histocompatibility complex class II genes (Dionne et al .…”
Section: Discussionmentioning
confidence: 90%
“…The genetic boundary between P. matsumurae in Central Honshu and the northern regions corresponds to that found by phylogeographic studies of several alpine plant species belonging to various taxa in Japan (e.g., Fujii et al., ; Ikeda et al., , , ; Hirao et al., ). This genetically disjunct structure in multiple alpine plant species strongly suggests historical isolation of alpine plant communities between Central Honshu and the northern regions during past climate oscillations (reviewed by Fujii and Senni, ).…”
Section: Discussionsupporting
confidence: 78%
“…However, a broad‐scale approach with a historical (phylogeographic) perspective is required to infer the evolutionary history of ecotype differentiation. Phylogeographic studies on Japanese alpine flora have demonstrated the existence of distinct lineages in Central Honshu and northern populations across multiple alpine plant species (e.g., Fujii et al., ; Fujii and Senni, ; Ikeda et al., , ; Hirao et al., ), including P. matsumurae (Ikeda et al., , ). On the basis of these findings, it has been proposed that the mountains of Central Honshu serve as refugia during historical climatic oscillations and populations in this area have been historically isolated from the populations of the more northern regions (reviewed by Fujii and Senni, ).…”
mentioning
confidence: 99%
“…The general large‐scale scenario based on the concept of southern refugia is especially altered when considering cold‐adapted (mountainous and arctic‐alpine) species (Birks & Willis, ; Eidesen et al., ; Hirao et al., ). The habitat availability and dynamics of populations in the mosaic of the European LGM periglacial areas depended substantially on species’ ecology.…”
Section: Introductionmentioning
confidence: 99%